Subpopulation-Specific Transcriptome Analysis of Competence-Stimulating-Peptide-Induced Streptococcus mutans - Lemme, André (American Society for Microbiology, 2011)
Competence-stimulating-peptide (CSP)-mediated competence development in Streptococcus mutans is a transient and biphasic process, since only a subpopulation induces the expression of ComX in the presence of CSP, and the activation of the DNA uptake machinery in this fraction shuts down ∼3 to 4 h postinduction. Here, we combine for the first time, to our knowledge, the bacterial flow-cytometric sorting of cells and subpopulation-specific transcriptome analysis of both the competent and noncompetent fraction of CSP-treated S. mutans cells. Sorting was guided by a ComX-green fluorescent protein (ComX-GFP) reporter, and the transcriptome analysis demonstrated the successful combination of both methods, because a strong enrichment of transcripts for comX and its downstream genes was achieved. Three two-component systems were expressed in the competent fraction, and among them was ComDE. Moreover, the recently identified regulator system ComR/S was expressed exclusively in the competent fraction. In contrast, the expression of bacteriocin-related genes was at the same level in all cells. GFP reporter strains for ComE and CipB (mutacin V) confirmed this expression pattern on the single-cell level. Fluorescence microscopy revealed that some ComX-expressing cells committed autolysis in an early stage of competence initiation. In viable ComX-expressing cells, the uptake of DNA could be shown on the single-cell level. This study demonstrates that all cells in the population respond to CSP through the activation of bacteriocin-related genes. Some of these cells start to activate ComX expression but then segregate into two subpopulations, one becoming competent and another one that lyses, resulting in intrapopulation diversity.